156. Direct Detection and Quantification of Bacterial Cell-free DNA in Patients with Infective Endocarditis (IE) Using the Karius Plasma Next Generation Sequencing (NGS) Test. (26th November 2018) - Shah, Pratik; Ruffin, Felicia; Seng, Hon; Hollemon, Desiree; Winn, Laura; Drennan, Caitlin; Chan, Ka Lok; Quach, Huy; Blauwkamp, Timothy; Meshulam-Simon, Galit; Hong, David; Fowler, Vance G
Abstract: Background: The variable clinical presentation of IE requires a diagnostic tool that accurately detects a wide range of organisms, including in culture-negative (CN) scenarios. A sensitive molecular diagnostic assay that quantitates pathogen DNA could be a useful tool to diagnose IE and evaluate response to antimicrobial therapy. Methods: We prospectively enrolled 30 hospitalized adult patients evaluated for acute IE classified using the Duke Criteria. Residual plasma samples within 24 hours and/or fresh whole blood within 48–72 hours of enrollment blood culture were collected. Additional samples were collected every 2–3 days for up to 7 time points until discharge. Samples were shipped to the Karius laboratory (Redwood City, California) for testing. Cell-free DNA was extracted and NGS was performed. Human sequences were removed and remaining sequences were aligned to a curated pathogen database of over 1, 000 organisms. Organisms present above a predefined statistical threshold were reported. Quantity of DNA for each reported pathogen was expressed as molecules per microliter. Results: Of 29 patients eligible for analysis, 18 had prosthetic valves and 7 had implanted cardiac devices. Twenty-four patients had Definite IE. Twenty patients had positive blood cultures (including S. aureus, S. epidermidis, E. faecalis, S. agalactiae, Pantoea ananatis, S. sanguinis, C. albicans ); NGS identified the same organism isolated in all 20 patients as well as E. cloacae complex, and E. faecalis in 2 of 4 CN Definite IE patients. For 1 CN patient with Possible IE, NGS identified E. coli. NGS and BC were negative for 4 patients with Rejected IE. NGS identified the IE etiology in patients pretreated with antibiotics up to 20 days prior to sample collection. Pathogen DNA signal was often observed in both initial and repeat plasma samples, while repeat blood cultures remained negative. Conclusion: This novel, cell-free pathogen quantitative NGS plasma assay accurately identified causative organisms in patients with IE, even when blood cultures were negative due to pretreatment with antibiotics. Pathogen DNA, detected in plasma longer than blood culture, is a promising biomarker to aid in the diagnosis and monitoring of IE, particularly culture-negative IE. Disclosures: P. Shah, Karius Inc.: Collaborator and Research Contractor, Salary. F. Ruffin, Karius Inc.: Collaborator and Research Contractor, Salary. H. Seng, Karius Inc.: Employee, Salary. D. Hollemon, Karius Inc.: Employee, Salary. L. Winn, Karius Inc.: Collaborator and Research Contractor, Salary. C. Drennan, Karius Inc.: Collaborator and Research Contractor, Salary. K. L. Chan, Karius Inc.: Employee, Salary. H. Quach, Karius Inc.: Employee, Salary. T. Blauwkamp, Karius Inc.: Employee, Salary. G. Meshulam-Simon, Karius Inc.: Employee, Salary. D. Hong, Karius Inc.: Employee, Salary. V. G. Fowler Jr., Merck, Cerexa/Actavis, Pfizer, Advanced Liquid Logis, NIH, MedImmune, Basilea, Karius, Contrafect, Regneron, Genentech, Affinergy, Locus, Medical Surface, Inc., Achaogen, Astellas, Arsanis, Bayer, Cubist, Debiopharm, Durata, Grifols, Medicines Co, Novartis: Collaborator, Consultant and Scientific Advisor, Consulting fee, Research grant and Research support.